Correlation of Sokal Scoring System with Molecular Response in pts of CML Taking CML Specific Tyrosine Kinase Inhibitors - Amna Shoukat, Aisha Nasir, Hafiz Muhammad Matloob, Aiza Asghar, Ayesha Iqbal, Amber Haroon, Talha Laique, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Chronic myeloid leukemia (CML) is a clonal myelo-proliferative disorder of a pluripotent stem cell. Aim: To find the frequency of low, intermediate and high risk category in patients of chronic myeloid leukemia and to compare frequency of complete molecular response. Study design: Descriptive case series. Methodology: Present study was conducted at Hematology Department, Sheikh Zayed Hospital Lahore. 260 patients fulfilled the selection criteria were selected. Sokal score was calculated. Low risk, intermediate and high risk category was assessed. Patients were followed up for 3 months. BCR-ABL translocation detection was done after 3months of treatment and complete molecular response was recorded. All this information was recorded on proforma. Data was analyzed using SPSS version 20. The chi-square test was used to compare the groups. A p-value of 0.05 was considered significant. Results: The mean age of patients was 49.18±20.33years. There were 144(55.4%) males and 116(44.6%) females. The mean duration of CML diagnosis was 3.52±1.69months. At baseline, 172 (66.2%) had low risk, 76(29.2%) had intermediate risk and 12 (4.6%) had high risk. In the study, complete molecular response was observed in 0% patients. Conclusion: It was concluded that there is regression in grades of Sokal score in patients of Chronic myeloid leukemia after 3 months treatment with TKIs but there is no complete molecular response observed in any patient after 3 months of treatment with TKIs.